Del héroe épico al héroe trágico: la progresión de los planteamientos éticos en la "Ilíada" - Morenilla, Carmen (2017)
In the Iliad, the main heroic characters undergo a transition from a culture in which mankind is left in the hands of the gods, or of an unquestionable fate, to a position in which the human being assumes his responsibility in the setting of an interaction between the human and the divine levels, a position where Aeschylus’ heroes, as well as those in Sophocles and Euripides, will behave in accordance with their respective dramatic premises.
Keywords: Homero; Héroes; Ética; Mitología griega